2023
DOI: 10.3390/v15091829
|View full text |Cite
|
Sign up to set email alerts
|

CSF Inflammation Markers Associated with Asymptomatic Viral Escape in Cerebrospinal Fluid of HIV-Positive Individuals on Antiretroviral Therapy

Debjani Guha,
Vikas Misra,
Jun Yin
et al.

Abstract: HIV establishes a viral reservoir in the CNS despite viral suppression in the blood on antiretroviral therapy (ART). In a minority of people with HIV (PWH), HIV RNA is detectable in CSF when HIV RNA in plasma is undetectable or HIV RNA levels are higher in CSF compared with plasma, an event termed CSF viral escape that can occur with or without neurological symptoms. Asymptomatic CSF viral escape occurs in 3–20% of PWH on ART, yet associated biomarkers are unclear. To identify biomarkers associated with asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Because of the striking findings of low IL-10 and IL-4 as independent risk factors for iHAM, and the predictive power of IL-10 for posterior PVL dynamics, we further explored the possible upstream and downstream mechanisms by examining a large panel of 37 pro-and anti-inflammatory cytokines, chemokines and immune mediators. Of those 37, seven were previously suggested as candidate biomarkers and/or therapeutic targets (MMP-1/2/3, TNFR1/2, IL-22, Osteopontin) ( 16 24 ) in HAM, while most of them were not previously interrogated at the protein level in HAM patients but have been demonstrated in other neuroinflammatory or neurodegenerative disorders, such as CHI3L1 (also known as YKL-40) in HIV-Associated Neurocognitive Decline (HAND) ( 25 ). Since only 64 out of 110 plasma samples were available (of which 6/9 iHAM) for these additional assays, we considered this an exploratory analysis because of the lower sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the striking findings of low IL-10 and IL-4 as independent risk factors for iHAM, and the predictive power of IL-10 for posterior PVL dynamics, we further explored the possible upstream and downstream mechanisms by examining a large panel of 37 pro-and anti-inflammatory cytokines, chemokines and immune mediators. Of those 37, seven were previously suggested as candidate biomarkers and/or therapeutic targets (MMP-1/2/3, TNFR1/2, IL-22, Osteopontin) ( 16 24 ) in HAM, while most of them were not previously interrogated at the protein level in HAM patients but have been demonstrated in other neuroinflammatory or neurodegenerative disorders, such as CHI3L1 (also known as YKL-40) in HIV-Associated Neurocognitive Decline (HAND) ( 25 ). Since only 64 out of 110 plasma samples were available (of which 6/9 iHAM) for these additional assays, we considered this an exploratory analysis because of the lower sample size.…”
Section: Resultsmentioning
confidence: 99%
“…Hermansson et al [ 32 ] found that YKL-40 concentrations in CSF did not differ between participants with and without HIV. Guha and colleagues [ 33 ] recently also observed no significant difference in plasma or CSF concentrations of YKL-40 by HIV status, but significantly higher YKL-40 in CSF (compared to people without HIV) specifically in people with HIV with a CSF HIV viral load higher than 50 copies/mL [ 34 ]. Notably, these studies were carried out in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection is associated with immune responses that include increased circulating cytokine levels in the periphery and within the central nervous system (CNS), and which may contribute to severity of disease (Merrill and Chen, 1991). Although ART can effectively maintain HIV-1 viral load at undetectable levels and prolong lifespan of PLWH, ART does not completely eliminate infection or the impact of HIV-induced immune response peripherally or within the central nervous system (CNS) on comorbidities including HIV-associated neurocognitive disorder (HAND) (Valcour et al, 2012;Ripamonti and Clerici, 2021;Guha et al, 2023).…”
Section: Introductionmentioning
confidence: 99%